An Interprofessional Approach to Advance Care Planning. (March 2022) - Kwak, Jung; Jamal, Aleena; Jones, Barbara; Timmerman, Gayle M.; Hughes, Brian; Fry, Liam
Context: Advance care planning (ACP) can improve patients' outcomes at end of life, and interprofessional collaboration has been recommended to facilitate ACP. However, role confusion in ACP facilitation among team members from different disciplines exists, and health professional disciplines' expectations for interprofessional collaboration in ACP are unclear. Objective: To review expectations of major health professional organizations for ACP competencies, in order to identify gaps and opportunities for promoting interprofessional collaboration in ACP facilitation. Methods: Guidelines and recommendations for ACP across disciplines including chaplaincy, medicine, nursing, psychology, and social work were identified and analyzed using content analysis. Main themes were then reviewed against national consensus statements on 4 ACP outcomes (process outcomes, action outcomes, quality of care outcomes, and healthcare outcomes) and mapped into existing domains for interprofessional education competency: values/ethics, roles/responsibilities, interprofessional communication, and teams and teamwork. Results: Three major content themes were identified: professional commitment to advocating for patients' values and self-determination, professional responsibility to facilitate ACP, and specific tasks in ACP. These themes addressed mostly process and action outcomes of ACP but not quality of care outcomes or healthcare outcomes. Few disciplines included interprofessional collaboration as part of ACP competency. Conclusion: There is a need for standardized competency guidelines for interprofessional collaboration in ACP as an important first step in reducing confusion among roles and other challenges in facilitating ACP. Further efforts in practice, research, and policy are needed to facilitate interprofessional ACP, achieve competencies, and improve patients' outcomes.